Math, asked by insiyahr, 1 year ago

Q7 (A) plz solve with steps

Attachments:

Answers

Answered by TPS
4
( {x}^{2} + 2x + 1)( {x}^{2} - 3x + 7) \\ \\ \text{Use distributive property: }\\ \\ = {x}^{2} ( {x}^{2} - 3x + 7) + 2x( {x}^{2} - 3x + 7) + 1( {x}^{2} - 3x + 7) \\ \\ = {x}^{2} \times {x}^{2} - {x}^{2} \times 3x + {x}^{2} \times 7 \\ + 2x \times {x}^{2} - 2x \times 3x + 2x \times 7 \\ + 1 \times {x}^{2} - 1 \times 3x + 1 \times 7 \\ \\ = {x}^{4} - 3 {x}^{3} + 7 {x}^{2} \\ + 2 {x}^{3} - 6 {x}^{2} + 14x \\ + {x}^{2} - 3x + 7 \\ \\ = {x}^{4} - 3 {x}^{3} + 2 {x}^{3} + 7 {x}^{2} - 6 {x}^{2} + {x}^{2} + 14x - 3x + 7 \\ \\ = \boxed{ \red{ {x}^{4} - {x}^{3} + 2 {x}^{2} + 11x + 7}}
Similar questions